THE INTEGRATION OF STRATEGIC DECISION-MAKING AND REWARD MANAGEMENT IN ENHANCING EMPLOYEE MOTIVATION - Amiraxon Sheraliyeva G’anijon qizi,; Inomjon Qudratov,; Budhi Pamungkas Gautama, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
One significant determinant of successful implementation of organizations' strategic plans and achievement of their intended outcomes is motivation of the workforce. Integrating strategic decision-making and a proper reward system is one way suggested as an efficient approach to improving employee motivation. In that regard, this study seeks to evaluate the relationship between strategic decision-making process and the implementation of a reward management system in order to motivate employees effectively. A quantitative research design was adopted whereby data were gathered using a questionnaire survey among employees in the chosen organization. The data collected from employees were subjected to inferential statistics to assess the relationship between strategic decision making and reward management. It was found out that participative, transparent, and performance-based strategic decision-making process has a significant influence on reward management. On the other hand, fair reward management in line with the organizations' strategic plans increases employees' extrinsic and intrinsic motivation levels. It can be concluded that strategic decision-making process and reward management are effective not only as administrative tools but also as motivational strategies. This study will make both theoretical and practical contribution into strategic management discipline.